A Comparative Analysis of Credit Performance Between Nabil Bank Limited and Nepal Bank Lim - Bista, Purushotam; Sigdel, Sahadev (Journal of Kathmandu BernHardt College, 2022)
This study conducts a comprehensive comparison of the credit performance of NABIL Bank Limited and Nepal Bank Limited, with a focus on analyzing the impact of specific credit variables on their profitability. The research uses financial instruments to enhance the effectiveness and educational value of the investigation. Through descriptive and analytical research, the study examines how credit-specific factors influence the profitability of both banks. The study utilizes various quantitative factors, including Return on Assets (ROA), Return on Equity (ROE), Loan and Advance to Total Deposit, Loan Loss Provision to Loan and Advance, Non-Performing Loan to Loan and Advance (NPLLA), and Loan Loss Provision to Non-Performing Loan (LLPNPL). It employs correlation and linear multiple regression analysis on secondary data spanning a ten-year period from 2010/11 to 2019/20. The significance of these relationships is tested at a 95% level of significance. The findings reveal that the variables used in the study are more effective in explaining the ROA for NABIL Bank Limited compared to Nepal Bank Limited, as indicated by the higher R2 value for NABIL Bank Limited. Notably, NPLA and LLPNPL have the most positive impact on NABIL Bank Limited's ROA, even though they are statistically insignificant at the 5% level. Conversely, LLPLA and LLPNPL have the most negative impact on the profitability of Nepal Bank Limited, but they also show insignificance at the 5% level of significance.